2020
DOI: 10.1093/europace/euaa189
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long-term mortality after catheter ablation of ventricular tachycardia in a contemporary cohort of patients with structural heart disease

Abstract: Aims Ablation of ventricular tachycardias (VTs) in patients with structural heart disease has been established in the past decades as an effective and safe treatment. However, the prognosis and long-term outcome remains poor. Methods and results We investigated 309 patients with ischaemic cardiomyopathy (ICM) and non-ischaemic cardiomyopathy (NICM) (186 ICM, 123 NICM; 271 males; mean age 64.1 ± 12 years; ejection fraction 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The methodology of the ablation has been described in detail elsewhere 10 . Put briefly, femoral venous vein access was used to place one decapolar catheter in the coronary sinus and one quadripolar catheter in the right ventricular apex.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology of the ablation has been described in detail elsewhere 10 . Put briefly, femoral venous vein access was used to place one decapolar catheter in the coronary sinus and one quadripolar catheter in the right ventricular apex.…”
Section: Methodsmentioning
confidence: 99%
“…[ 10 ] report 41% of patients reaching the primary endpoint of assist device/HTX or death after 1.2 years of follow-up. Accordingly, the present authors reported in their published study [ 11 ] a mortality rate of 31% with 5% of patients undergoing an LVAD implantation and 3% receiving HTX, reaching to a combined endpoint of LVAD/HTX or death of 36% within the 4‑year follow-up.…”
Section: Discussionmentioning
confidence: 86%
“…The methodology of the procedure has been described in detail elsewhere [ 11 ]. In brief, after deep sedation, femoral vein access was used to place one decapolar catheter in the coronary sinus and one quadripolar catheter in the right ventricular apex.…”
Section: Methodsmentioning
confidence: 99%
“…During 2012–2015, 309 patients with SHD underwent one or multiple VT‐ablations in our center. For the purpose of the analysis, we only compared patients younger than 75 years in reference 8 to our current cohort. When compared to the 241 patients under 75 years, the 68 geriatric patients had similar results concerning noninducibility as the endpoint (86% vs. 85%; p = .911) and arrhythmia recurrence (45% vs. 34%; p = .113).…”
Section: Discussionmentioning
confidence: 99%
“…The methodology of the ablation has been described in detail elsewhere 8 . In brief, femoral venous vein access was used to place one decapolar catheter in the coronary sinus and one quadripolar catheter in the right ventricular apex.…”
Section: Methodsmentioning
confidence: 99%